Tax aggressiveness of family firms in emerging countries: How does resource-based view explain it? - Usil Sis Sucahyo; Theresia Woro Damayanti; Ronny Prabowo; Supramono (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to empirically examine the effects of three resource categories based on the resource-based view - represented by firm size, top manager's experience, and closeness to governments - on family firms tax aggressiveness in emerging countries. Research Design & Methods: The study used data from the World Bank's Productivity and the Investment Climate Survey that covers several issues, including taxation. The survey was held in 2006-2018. We use data from 19 848 family firms as our sample. Data is analysed with the Ordered Probit Model. Findings: The results of the analysis showed that family firms with resources of firm size, top manager's better experience, and closeness to government have the options to engage in greater tax aggressiveness than other family firms. Implications & Recommendations: The governments of emerging countries need to pay more attention to larger family firms and the firms led by more experienced top managers to enhance tax compliance because these firms potentially engage in greater level of tax aggressiveness. Contribution & Value Added: This study offers a better understanding of the tax aggressiveness of family firm that is relatively poorly understood in the literature with the resource-based view approach.
Keywords: L14; H26; 330; tax aggressiveness; family firms (FFs); resource-based view (RBV); firm size; top manager's experience; closeness to governments